Van Buchem Disease: First Case Report from the Indian Subcontinent with an Early Presentation - Maheshwari, Saurabh; Yangzom, Sonam; Bhanu, K. Uday; Rajesh, Uddandam; Narayan, Ashok (Journal of Child Science, 2021)
Van Buchem disease is a rare autosomal recessive genetic disorder that causes a compromised inhibitory feedback mechanism resulting in increased bone formation and overgrowth of the skeleton leading to a variety of neurological symptoms. It has been reported in less than 50 patients most of which were in western Europe. We report the first case of this condition from the Indian subcontinent with an early presentation. This patient presented with a global delay in attaining the developmental milestones and progressive reduction in visual acuity and loss of hearing. He had dysmorphic facies, multiple cranial nerve palsies, and severe visual and auditory deficits. Imaging revealed sclerosing bone dysplasia. This case illustrates the clinical and imaging findings of this rare condition.
Keywords: Van Buchem disease; cranial nerve; hyperostosis corticalis generalisata